Green energy: Fueling the path to food security - Arndt, Channing; Msangi, Siwa; Thurlow, James (International Food Policy Research Institute, 2016)
Energy is vital to the global food system and food security, but countries will need to explore greener energy paths to address climate change. Opportunities for achieving both green energy and food security goals include solar and hydropower in Africa, biofuels in poor countries, and energy-saving cookstoves.